Customer Journey Experience and Its Effect on PT KAI’s Brand Equity - Anisa Silviana Putri; Andreas Rio Adriyanto; Dandi Yunidar (Dinasti International Journal of Education Management and Social Science, 2025)
The digitalisation of railway services in Indonesia has significantly altered passengers’ travel behaviour, although non-digital touchpoints remain essential for users with diverse levels of digital proficiency. This study investigates user interactions with PT Kereta Api Indonesia (KAI) across the pre-trip, on-trip, and post-trip stages, and analyses how these interactions shape perceptions of service quality and contribute to the formation of brand equity. Employing a qualitative descriptive approach grounded in service design, the research utilises contextual inquiry to capture actual user behaviour at Bandung and Gambir Stations. Field observations were complemented by questionnaire data from respondents to identify patterns in information search, ticket purchasing, station navigation, and engagement with digital features such as face-recognition gates. The results indicate that digital touchpoints facilitate efficient access to schedules, ticketing, and payments, yet users continue to rely on physical guidance, staff support, and clear environmental cues to navigate the service ecosystem effectively. The degree of coherence between digital and physical touchpoints throughout the customer journey substantially influences user satisfaction and plays a critical role in strengthening KAI’s brand equity.